(3eaQL GdfaSs - (3HOQ GdOjf eXaQ Hf YHO GdQMef Hf EHQGgje GdHYdHcj GdOeTbj, GHf bGVj HYdHc,J (B675 (3g` s ((3eOjfI WQGHdS GdSGMd s)
(3ChdgG (B:s
(3CeG HYO MeO Gddg NGdb GdOGA hGdOhGA hGdefbP ef GdCeQGV hGdCOhGA aEfi deG EWdYJ Ydi CcKQ GdcJH GdWHjI ade CLO ajgG eG jTai GdfaS ai PcQ GdCehQ GdeaQMI HGH ai PcQ GdfaS hHYV CMhGdgG s
(3BNQgG (B:s
(3eG jNJGQg hjghGg ef Ci Ufa cGf ef GdehLhOGJ aPdc ef Cced GdeaQMGJ (B( (3GdHGH GdYGTQ ai GddPi GdecJSHI ddfaS ef GdMhGS GdHGWfjI (B) s
(3ai GdCOhjI hGdCTjGA GdbdHjI Ydi ENJdGagGs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1772s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdWHs